1979
DOI: 10.1177/000331977903000311
|View full text |Cite
|
Sign up to set email alerts
|

Prinzmetal's Variant Angina Associated With Subarachnoid Hemorrhage: A Case Report

Abstract: Prinzmetal's variant of angina occurred in a 48-year-old man who sustained two attacks of subarachnoid hemorrhage within 10 days. The first anginal pain started at the same time that the second cerebrovascular accident developed, but subsequent anginal episodes were not accompanied by other symptoms or signs that indicated new development of subarachnoid hemorrhage. Twelve days later, when nuchal rigidity was fairly improved, the episodes of chest pain ended. A vasospasm of the large coronary arteries--probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…33 Although reversible myocardial contractile dysfunction ("stunning") can also result from ischemia associated with coronary artery atherosclerosis or vasospasm, 2 this process would be expected to correspond closely to one or more arterial territories. Coronary artery vasospasm has been postulated as a possible mechanism of cardiac injury in SAH, 43,47 but has never been documented. Nontransmural subendocardial infarction related to microvascular compromise and increased myocardial demand may also explain the clinical findings in our patients, and in one autopsy study was identified as the cause of apical septal hypokinesis in a patient with SAH.…”
Section: Mechanism Of Neurogenic Cardiac Injurymentioning
confidence: 99%
“…33 Although reversible myocardial contractile dysfunction ("stunning") can also result from ischemia associated with coronary artery atherosclerosis or vasospasm, 2 this process would be expected to correspond closely to one or more arterial territories. Coronary artery vasospasm has been postulated as a possible mechanism of cardiac injury in SAH, 43,47 but has never been documented. Nontransmural subendocardial infarction related to microvascular compromise and increased myocardial demand may also explain the clinical findings in our patients, and in one autopsy study was identified as the cause of apical septal hypokinesis in a patient with SAH.…”
Section: Mechanism Of Neurogenic Cardiac Injurymentioning
confidence: 99%
“…Other authors have described a case of Prinzmetal's angina associated with subarachnoid hemorrhage. 7 Our case, however, illustrates that, in rare instances, myocardial injury can follow damage to the rostral ventrolateral medulla. We felt surgery was not contraindicated because of the normal findings on coronary angiogram but a risk of increased harm existed.…”
mentioning
confidence: 62%
“…One of the possible mechanisms of cardiac dysfunction is ischemia resulting from coronary thrombosis or epicardial coronary artery spasm [36,37]. Another possible mechanism is microvascular vasospasm because microvascular vasospasm or dysfunction could not be evaluated angiographically.…”
Section: Discussionmentioning
confidence: 99%